2015
DOI: 10.1007/s10157-015-1144-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of urinary liver-type fatty acid-binding protein as a predictor of ESRD and CVD in patients with CKD

Abstract: Urinary L-FABP may be a useful prognostic marker of progression to ESRD and the onset of CVD in patients with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
2
29
0
1
Order By: Relevance
“…CVD is the critical cause of mortality in PD and HD patients. 8 Extracellular fluid volume overload and hypertension are the most common pathogenesis which result in myocardial hypertrophy. 9 Calcium concentration was reported to be an important factor in the development of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…CVD is the critical cause of mortality in PD and HD patients. 8 Extracellular fluid volume overload and hypertension are the most common pathogenesis which result in myocardial hypertrophy. 9 Calcium concentration was reported to be an important factor in the development of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…To precisely evaluate the degree of renal injury using the marker urinary liver-type fatty acid-binding protein (L-FABP) (11), human L-FABP chromosomal transgenic (Tg) mice (12) in which human L-FABP was expressed in proximal tubules of the cortex were used, because L-FABP is not expressed in mouse kidneys (37). Because urinary L-FABP accurately reflects the degree of oxidative stress, peritubular blood flow, and tubulointerstitial damage (14 -16), it is a novel tubular marker to predict renal prognosis in CKD (11,13,19) or for early detection of diabetic nephropathy (1,16,27) and acute kidney disease (acute kidney injury) (20,32,39) in clinical practice.…”
mentioning
confidence: 99%
“…b Correlation between ischemic time and urinary L-FABP. R indicates correlation coefficient [36] disease (CKD) [53] or those who have undergone cardiac catheterization [54,55] or renal transplantation [56,57]. Clinical prospective observation studies to predict mortality in sepsis using urinary L-FABP have been conducted with both adult patients and pediatric patients (Table 3) [27,28].…”
Section: Predicting Poor Outcomesmentioning
confidence: 99%
“…It is important to measure the higher range near 100 ng/ml for ICU patients because it was suggested that upper levels of urinary L-FABP than 100 μg/g Cr may be specific to septic shock [25]. Additionally, it is also important to measure the range near 12.5 ng/ml for CKD patients because it was reported that levels of urinary L-FABP above the upper limit of the reference value (8.4 μg/g Cr [6]) are a risk factor for the progression to ESRD, the onset of cardiovascular disease CVD, and death [53]. When we reanalyzed reference value to L-FABP concentration, the reference value which converted to L-FABP concentration was 10.1 ng/ml.…”
Section: Clinical Significance Of the Poc Assay For Urinary L-fabpmentioning
confidence: 99%